Estetika v (životě a) díle Konrada Lorenze: Aneb Když jde o dobrý vkus... - Stibral, Karel; Stella, Marco (Lidé města, 2006)
We would like to state at the outset that this article is not only a reaction to Zdeňek Pinc’s article, dated 2004, but also a contribution to further discussions. That is the reason it is composed of two parts – the first one is, as the section’s title suggests, reaction to Zdeňek Pinc’s contribution to the Lorenz topic, the second and longer part is our attempt to scrutinize this issue from somewhat different point of view. In his article Few comments by a non-biologist on Stanislav Komárek’s reviews, Pinc expresses, totally justifiably, astonishment and partly also dismay about certain facts regarding involvement of Konrad Lorenz in theory and practice of racial measures instituted by the Third Reich. It might possibly seem that this is a singular and unprecedented problem (Nobel price laureate and at the same time Parteigenosse Nr. 6170554?). However, recent years indicate that the issue of use and misuse of biology, anthropology and other scientific disciplines in the name of Nazism is much more extensive, more complex and sometimes also more atrocious than we have, up to now, anticipated or hoped for. This is collaborated by the volume of recent or less recent publications. In this country, it is not customary to study this issue and Zdeněk Pinc totally justifiably and at the right time has urged “to turn attention of researchers in this direction“ – west of our borders, the interest in this topic is slowly diminishing and moreover archives and libraries in the former Eastern Block countries contain many surprises still awaiting their disclosure.